The Role of Family in Career Development of Secondary Schools' Students in Khyber Pakhtunkhwa, PakistanThe study aimed to investigate the role of family in career development of secondary schools’ students in Khyber Pakhtunkhwa, Pakistan. Study’s objectiv - Zeb, Alam; Ali, Arshad; Hussain, Mian Said (Pakistan Languages and Humanities Review, 2025)
The study aimed to investigate the role of family in career development of secondary schools’ students in Khyber Pakhtunkhwa, Pakistan. Study’s objectives were to find out the role of family in career development of students at secondary level. Its population was 30439 students. Its sample 380 was selected with selected with simple random sampling. A questionnaire was developed, validated and pilot tested for collecting data. Data were gathered with self-administered questionnaires and analyzed with using mean scores, standard deviations and chi-square test. The study found significant effect of family on students’ career development at secondary level. Families selected their subjects for study, informed them about careers, supported financially and assist them through coaching academies. The study recommended availability of career guidance facilities in schools. Additionally, family and school may collaborate for effective career development of students.